Conversion of Pyrolysis Fuel Oils by a Dielectric Barrier Discharge Reactor in the Presence of Methane and Ethane. Issue 8 (27th May 2015) - Khani, Mohammad R.; Khosravi, Attieh; Gharibi, Mahtab; Shahabi, Seyedeh S.; Guy, Elham Dejban; Shokri, Babak
Abstract Pyrolysis fuel oil cracking by low‐temperature plasma was investigated in a dielectric barrier discharge reactor at ambient pressure. The promoting effect of methane and ethane in the formation of products was evaluated by altering the working gas from methane to ethane. In addition, the production of hydrocarbons and hydrogen was analyzed. The main parameters were working gas type, flow rate, and applied voltage. Increasing the applied voltage enhanced the production rate of valuable petrochemical compounds like gas and liquid. Alteration of the working gas flow rate led to a higher production rate of H2, C2, C3, and C4. Chemical investigations were performed by optical emission spectroscopy of plasma and the main mechanisms are described.